rs9789446 genotype as susceptibility biomarkers for congenital hypothyroidism based on population and family validation - Zhong, Xue; Jia, Yaning; Liu, Wenmiao; Qiao, Mengfei; Li, Miaomiao; Yu, Xiaolong; Liu, Shiguo (Frontiers in Genetics, 2025)
IntroductionCongenital hypothyroidism (CH) is a metabolic disorder in newborns due to insufficient synthesis, abnormal secretion, or defective action of thyroid hormones. While newborn screening enables early detection, the precise etiology remains elusive in most cases, with genetic factors playing a crucial but incompletely characterized role. This study comprehensively investigated the association of the rs9789446 polymorphism with CH risk, its interactions with biological sex and clinical subtypes, and its impact on thyroid function severity.MethodsA case-control study was conducted with 306 CH patients and 441 controls. Genotyping for rs9789446 was performed using SNPscan™. Association analyses included chi-square tests, logistic regression stratified by biological sex and clinical features, linear regression for thyroid parameters, and family-based validation in 201 trios using TaqMan™ assays.ResultsThe minor G allele frequency was significantly lower in CH patients (0.348) than in controls (0.407). A protective association was observed for the G allele against CH risk (OR = 0.78, p = 0.021), with a stronger effect in males under the dominant model (OR = 0.57, p = 0.008) but no association in females, highlighting a pronounced sex-specific effect. Stratification by permanent or temporary subtypes showed no significant association, while a modest effect was detected in the goitrous subgroup under the dominant model. Initial thyroid hormone levels exhibited no significant correlation. Importantly, family-based analyses robustly validated the case-control findings.DiscussionThe rs9789446 G allele confers a sex-specific protective effect against CH, particularly in males. This supports its potential utility in genetic risk assessment and personalized screening strategies for early intervention.